Impact of a Bayesian Individualization of Cyclosporine Dosage Regimen for Children Undergoing Allogeneic Hematopoietic Cell Transplantation: A Cost-Effectiveness Analysis. Issue 4 (August 2021) - Beyron, C.; Ceraulo, A.; Bertrand, Y.; Bleyzac, N.; Philippe, M.
Abstract : Background: Cyclosporine A (CsA) is the main drug used to prevent graft-versus-host disease in patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT). CsA therapeutic drug monitoring (TDM) has been performed for ages, with studies revealing clinical benefits, but failing to examine its economic impact. In this article, the main objective was to evaluate the economic impact of the CsA TDM strategy, based on a Bayesian approach, by assessing costs related to its clinical impact. Furthermore, TDM effectiveness was analyzed for pharmacokinetics and clinical outcomes. Methods: A cost-effective, nonrandomized, retrospective, single-center study compared 2 CsA monitoring and dose adaptation strategies in pediatric patients undergoing HSCT. From 2014 to 2016, CsA TDM was performed using a population pharmacokinetics model-coupled Bayesian approach by a pharmacist ["pharmacist-assisted individualization" (PAI)]. From 2017 to 2018, CsA TDM was performed by the clinician without a Bayesian approach (non-PAI group). HSCT costs were evaluated from the French National Insurance perspective. Economic and clinical outcomes were assessed by measuring incremental cost-effectiveness ratios. Results: The study included 144 patients: 90 and 54 patients in PAI and non-PAI groups, respectively. Both groups were comparable for sociodemographic and clinical characteristics. The mean total cost per patient was significantly lower ( P < 0.01) in the PAI group ([Euro sign]85, 947) than in the non-PAI group ([Euro sign]100, 435). Multivariate analysis revealed that TDM based on the Bayesian approach was a protective factor (odds ratio = 0.86) for severe acute graft-versus-host disease. We noted that pharmacist-based TDM was the dominant strategy. Bayesian method–based TDM allowed an increase in the percentage of target attainment at any period post-HSCT. Conclusions: CsA TDM with a Bayesian approach is a cost-effective procedure, and highlighted clinical benefits encourage the development of new TDM strategies for HSCT.